Educators’ experiences of teaching learners with hearing loss in inclusive classrooms - Hella M.T.E. Moustache; Musa Makhoba (South African Journal of Childhood Education, 2024)
Background: A global move towards inclusivity has made inclusive education (IE) a necessity. The education of the learner with hearing loss (HL) in an IE setting remains challenging and scarcely researched. Despite government’s clear position on IE, the extent to which the recommendations in the Education White Paper 6 (2001) (EWP6) are implemented, and the educator’s related experiences, remains limited, which inspired this study.